2006
DOI: 10.1038/sj.ejcn.1602553
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of αs1-casein hydrolysate on stress-related symptoms in women

Abstract: Objective: To examine the effects of a s1 -casein hydrolysate on females with stress-related symptoms. Design: Double-blind, randomized, crossover, placebo-controlled trial. Setting: The a s1 -casein hydrolysate was manufactured by INGREDIA (Arras, France) and the placebo was manufactured by DIETAROMA (Bourg, France). Study was designed and performed at PROCLAIM (Rennes, France), and the statistical analyses were performed by D Desor (Nancy, France). Subjects: A total of 63 female volunteers suffering from at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 26 publications
3
36
0
2
Order By: Relevance
“…Results from questionnaire-based studies show that a s1 -casein hydrolysate may be used as an effective functional ingredient alleviating stress-related symptoms after 30 days of administration in women (Kim et al, 2007) and after 56 days in cats (Beata et al, 2007). Our results showed that a CH diet administered for a period of 65 days reduced some stress-related indicators in dogs.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Results from questionnaire-based studies show that a s1 -casein hydrolysate may be used as an effective functional ingredient alleviating stress-related symptoms after 30 days of administration in women (Kim et al, 2007) and after 56 days in cats (Beata et al, 2007). Our results showed that a CH diet administered for a period of 65 days reduced some stress-related indicators in dogs.…”
Section: Discussionsupporting
confidence: 55%
“…Several of the parameters used in this study have been reported to characterize the different components of a stress reaction: questionnaires (Kim et al, 2007), endocrine assay (Ilardo et al, 2001) and physiological measurements (Boiten et al, 1994;Larson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy human volunteers, this tryptic hydrolysate showed anxiolytic-like effects, without side effects, on the basis of hemodynamic parameters under mentally and physically stressful situations [45]. A recent study showed that a 30-day ingestion of S1-casein tryptic hydrolysate decreased stress-related symptoms in women, particularly in digestive, cardiovascular, intellectual, emotional and social problems [46]. Thus, considering the deleterious link between stress, anxiety and sleep, we hypothesized that this S1-casein hydrolysate might also prevent or reduce the effects of stressful environmental conditions on sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Des peptides fonctionnels issus du lait tels que l'alpha-lactalbumine et l'alpha-1 caséine peuvent amélio-rer les performances cognitives de sujets vulnérables au stress [55] et les symptômes liés au stress [56]. Le recours aux méthodes de relaxation, de yoga, de sophrologie ou de méthodes apparentées (Vittoz) pourrait s'avérer utile.…”
Section: Orientations Thérapeutiquesunclassified